Mechanical Properties and Mullins Effect in Natural Rubber Reinforced by Grafted Carbon Black - Wen Fu; Li Wang; Jianning Huang; Cuiwen Liu; Wenlong Peng; Haotuo Xiao; Shenglin Li (Advances in Polymer Technology)
The obvious polarity difference between the carbon black (CB) and the natural rubber (NR) causes the CB hard to be dispersed in the NR matrix when the addition amount is large. In this paper, polyethylene glycol (PEG) was grafted onto the surface of CB by the liquid phase. The grafted carbon black (GCB) was prepared and applied to reinforce NR. The main physical and mechanical properties of NR were improved because of the better compatibility between GCB and NR. The Mullins effect of the vulcanizate was calculated by the cyclic stress-strain experiment. The results showed that the Mullins effect both existed in the virgin NR system and filled NR system. The degree of Mullins effect was increased with the increase of the filler addition, but that was different for CB and GCB. When the filler addition was below 20 phr, the Mullins effect of NR/GCB was stronger than that of NR/CB. However, when the filler addition was over 30 phr, the Mullins effect of NR/CB was stronger than that of NR/GCB. The Mullins effect was affected by the heat treatment temperature and time. The mechanisms of the Mullins effect were analyzed.